2019
DOI: 10.3390/s19010211
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu2O/CuO Nanocrystals and Their Application to H2S Sensing

Abstract: Semiconducting metal oxide nanocrystals are an important class of materials that have versatile applications because of their useful properties and high stability. Here, we developed a simple route to synthesize nanocrystals (NCs) of copper oxides such as Cu2O and CuO using a hot-soap method, and applied them to H2S sensing. Cu2O NCs were synthesized by simply heating a copper precursor in oleylamine in the presence of diol at 160 °C under an Ar flow. X-ray diffractometry (XRD), dynamic light scattering (DLS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 62 publications
2
20
0
Order By: Relevance
“…)(normalαnormalhnormalνn=Ahν-Enormalgwhere α is the absorption coefficient, hν is the photon energy, A is a constant, E g is the optical band gap of the material, and n = 2 for direct transitions. The (αhν) 2 ‐hν relation of CuO particles is shown as inset in Figure A, from which the direct band gap is found to be 1.8 eV, in close agreement with the literature …”
Section: Resultssupporting
confidence: 89%
“…)(normalαnormalhnormalνn=Ahν-Enormalgwhere α is the absorption coefficient, hν is the photon energy, A is a constant, E g is the optical band gap of the material, and n = 2 for direct transitions. The (αhν) 2 ‐hν relation of CuO particles is shown as inset in Figure A, from which the direct band gap is found to be 1.8 eV, in close agreement with the literature …”
Section: Resultssupporting
confidence: 89%
“…The current in the forward and reverse directions significantly reduced after exposure to H2S. We have recently confirmed that CuO NCs-based sensors respond to H2S by an increase in electrical resistance due to reaction of adsorbed oxygen with H2S, representing a typical behavior of p-type semiconductors [3]. Thus, the observed increase in resistance for the present device is possibly due to surface reaction of adsorbed oxygen with H2S and the resulting annihilation of holes.…”
Section: Resultssupporting
confidence: 77%
“…Both crystallite size and lattice constants are presented in Table 1. The particle size was calculated using Scherrer's equation [35] (Equation (2)), where D is the crystallite size in nm, λ is the Cu Kα radiation wavelength (1.5046 Å), K is the shape factor (0.9), β hkl is the full width at half maximum (FWHM) in radians, and θ is the scattering angle in radians. As seen in Table 1, crystallite size decreased as the applied potential in the BPE synthesis increased, with a minimum (14.5 nm) occurring at the maximum applied potential of 8.0 V. Similarly, by extending the reaction time from 1 to 3 h (sample synthesized at 4.5 V, red and blue patterns in Figure 1), crystallite size increased from 21.7 to 27.1 nm.…”
Section: Structural Analysis Of Cu 2 Omentioning
confidence: 99%